2000
DOI: 10.1002/1097-4547(20000715)61:2<162::aid-jnr7>3.3.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Manganese‐induced rat pheochromocytoma (PC12) cell death is independent of caspase activation

Abstract: Manganese (Mn) is an essential mineral that at high concentrations can produce an irreversible syndrome resembling Parkinson's disease. To examine the mechanism by which Mn elicits its toxic response, we have selected the rat pheochromocytoma cells (PC12) as our model system because it possesses much of the biochemical machinery associated with dopaminergic neurons. Mn-induced PC12 cell death is both time and concentration dependent with approximately 50% cell survival at 48 hr in the presence of 0.3 mM Mn. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Mn exposure has been also shown to cause neurotoxicity in vitro and in vivo . Excessive Mn induces oxidative stress in the brain to exacerbate mitochondrial dysfunction and stimulates ER stress‐mediated apoptosis in rat striatum neurocytes . In previous research, we also found Mn can induce mitochondrial dysfunction in SH‐SY5Y cells .…”
Section: Introductionmentioning
confidence: 70%
“…Mn exposure has been also shown to cause neurotoxicity in vitro and in vivo . Excessive Mn induces oxidative stress in the brain to exacerbate mitochondrial dysfunction and stimulates ER stress‐mediated apoptosis in rat striatum neurocytes . In previous research, we also found Mn can induce mitochondrial dysfunction in SH‐SY5Y cells .…”
Section: Introductionmentioning
confidence: 70%
“…2008; Zhang et al, 2007). However, apoptosis-independent cell death has also been observed in one study, suggesting that apoptosis is not the only cell death mechanism triggered by Mn (Roth et al, 2000).…”
Section: Manganesementioning
confidence: 86%
“…Apoptotic cell death is the most-reported key downstream event regarding Mn-induced neurotoxicity (Chun et al, 2001b;Desole et al, 1996;Desole et al, 1997;Hirata et al, 1998;Latchoumycandane et al, 2005;Malecki, 2001;Roth et al, 2000;Xu et al, 2014). The activation of apoptosis as well as increased oxidative stress in microglia appeared to be dependent on the activation (via phosphorylation) of MAP kinases JNK and ERK (Bae et al, 2006;Hirata et al, 1998;Yin et al, Supporting publications 2016: EN-955 76 The present document has been produced and adopted by the bodies identified above as authors.…”
Section: Manganesementioning
confidence: 89%
See 1 more Smart Citation
“…Caspases are cysteine proteases that cleave a critical set of cellular Pr to initiate the apoptotic signal including several representatives involved in apoptosis (Roth et al, 2000;Tsujimoto and Shimizu, 2000;Gogvadze and Orrenius, 2006). According to the substrate specificities and target Pr, caspases are grouped into ''apoptotic initiator'' such as caspase-9, and ''apoptotic effector'' including caspase-3 (Kaufmann and Hengartner, 2001).…”
Section: Discussionmentioning
confidence: 99%